Penggunaan Video Based Laboratory (VBL) dalam Menentukan Nilai Modulus Elastisitas Penggaris Aluminium - Astuti, Irnin Agustina Dwi; Sumarni, Ria Asep; Bhakti, Yoga Budi (UPEJ Unnes Physics Education Journal, 2018)
This study aims to determine the value of elastic modulus of aluminum rod using Video Based Laboratory (VBL) and tracker analysis. The subject discussed about the material of elasticity, because the material is still abstract and still related to everyday life. To overcome these problems then created a learning innovation in the form of innovative visual aids that can attract students' responses in physics learning. Experiments are a planned effort to answer a question by creating an activity under controlled conditions. This tool consists of an aluminum ruler, load, slide, micrometer couplers, couplers, balance sheets, laptops, and cameras. The load used in the research varied as much as six loads with mass of 8.5 grams; 16.3 grams; 22.7 grams; 30.6 grams; 38.0 grams; And 45.8 grams. The method used is linear regression analysis the relationship between the square of the period of T2 oscillation to the load mass M and the data collection for the determination of the modulus value of elasticity of the material is done by ruler oscillation with variation of load mass in the video then analyzed by using tracker software. Furthermore, from T2 data to M is done by linear regression and obtained gradient value which will be used to determine modulus value of ruler elasticity. The value of the aluminum rod elastitis modulus (61.91 ± 5.69) × 109 N / m2 approximates the reference value of 70 × 109 N / m2 with a relative ration of 11.6%.